In-game monitoring of adolescent handball players: a preliminary examination of associations between external load parameters and objective and subjective fatigue markers - Bauer, J.; Muehlbauer, T.; Venzke, J.; Schäfer, R.; Platen, P.; Gruber, M. (Frontiers in Sports and Active Living, 2026)
Background: